The profundity and dynamism of Islamic architecture - Spahic, Omer (IIUM Journal Publication Unit, 2020)
This article discusses how profound and dynamic the world of Islamic architecture is. The article focuses on the issues of properly conceptualizing Islamic architecture, its genesis, the role of Islamic spirituality in it, and its relationship with both tradition and modernity. The article concludes that Islamic architecture is a microcosm of Muslims’ cultural and civilizational awareness and evolution. In order to ensure its timeless appeal, Islamic architecture embodies the principle of unity in diversity: the unity of Islamic worldview, purpose and values, and the diversity of shifting methods, procedures and styles. The problems concerning Islamic architecture today are chiefly relatable to the Muslim problems of ideas and values that form the soul of Islamic architecture. The problem of external manifestations are of secondary importance.